Clinical predictors of NEDA-3 one year after diagnosis of pediatric multiple sclerosis: an exploratory single-center study - Palavra, Filipe; Silva, Diogo; Fernandes, Catarina; Faustino, Ricardo; Vasconcelos, Mónica; Pereira, Cristina; Costa, Carmen; Ribeiro, Joana Afonso; Amaral, Joana; Robalo, Conceição (Frontiers in Neuroscience, 2023)
Introduction Multiple sclerosis (MS) is an inflammatory and demyelinating disorder of central nervous system that can be diagnosed in pediatric age (<18 years) in 3–5% of the cases. This early onset is associated with higher relapse rates and earlier progression to neurological disability. By using NEDA-3 (No Evidence of Disease Activity-3) criteria, we aimed to identify clinical predictors associated with absence of disease activity and control of disease progression 12 months after the diagnosis, in a cohort of pediatric-onset MS (POMS) patients regularly followed-up in our center. Methods We analyzed demographic, clinical, laboratorial and imaging variables of patients with POMS identified in our center, between 2010 and 2021, in two moments: at the diagnosis and 12 months after it. Statistical tests were applied to compare the distribution of those variables between groups defined by NEDA-3 status and by each one of its three variable components. Results We included 27 patients in the study (18 female), with a mean age of 14.8 years (± 2.8), being all diagnosed with relapsing–remitting MS and with a median score of 1.5 at the Expanded Disability Status Scale (EDSS). The use of natalizumab (p = 0.017) and the negativity for anti-EBV IgG antibodies (p = 0.018) at diagnosis were associated with a higher achievement of NEDA-3 status 12 months after, in our cohort. Prescribed treatment was also associated with statistically significant differences in the “absence of MRI activity” component of NEDA-3 (p = 0.006): patients under treatment with natalizumab had a higher probability of achieving this status, and the opposite was observed in glatiramer acetate-treated children. Discussion and conclusion Our exploratory results underline the pivotal importance that an early and more effective therapeutical approach may have in the control of disease activity, in POMS. Additionally, they also seem to suggest that the presence of anti-EBV antibodies is not innocent, as it can be related to a less favorable evolution of the disease, even at a very early stage. Further studies are needed to confirm the applicability of these variables as prognostic and personalized tools in this clinical setting.